ANALISIS EFISIENSI INDUSTRI KECIL BERDASARKAN ANALISIS STOCHASTIC FRONTIER - M. Farid Wajdi (Benefit: Jurnal Manajemen dan Bisnis, 2012)
The aimed of this study is to analyze the achievement of technical efficiency in smallbusinesses. The input factors that were analyzed are capital and worker, while the output factor is theproduct of the firm. Analysis using stochastic frontier. The result of analysis of technical efficiencyshow that the achievement of technical efficiency of enterprises of the study sample was quite goodcategory. While the returns to scale the firms are decreasing returns to scale (DRS). The role of capitaland worker aspects have little effect on improving the company’s production on the overall studysample. If the capital increase of 1% will be able to raise production by 0193%. whereas if there is theaddition of 1% of workers will increase production by 0005%. Based on the stochastic frontiertechnical efficiency analysis of each sub-sector that the handicraft sub-sector efficiency is highest.